KECERDASAN EMOSIONAL TERHADAP KOMITMEN ORGANISASI MELALUI KEPUASAN KERJA - Argon, Bill Argon; Liana, Yuyuk (JURNAL AKUNTANSI DAN INVESTASI, 2020)
In general, the purpose of this study is to determine whether there is a direct influence between emotional intelligence, job satisfaction on organizational commitment and the indirect effect between emotional intelligence on organizational commitment through job satisfaction. This research was conducted by all employees of PT. Digital Netwerk Venture Indonesia, which numbered 117 employees, and this study uses a correlational quantitative research method and uses a validity test, reliability test, and path analysis. The results of this study indicate that emotional intelligence has a positive and significant effect on organizational commitment of employees at PT. Digital Netwerk Venture Indonesia. Furthermore emotional intelligence has a positive and significant effect on employee job satisfaction. And job satisfaction has a positive and significant effect on organizational commitment. In addition, the results of this study also prove that there is a positive and significant influence between emotional intelligence on organizational commitment through job satisfaction. That means that Emotional Intelligence indirectly influences Organizational Commitment through Employee Satisfaction at PT. Digital Netwerk Venture Indonesia.